STUDI PEMANFAATAN Mo-ZAA SEBAGAI KATALIS DAN PENGARUH VARIASI TEMPERATUR HIDROCRACKING TERHADAP PRODUK HIDROCRACKING MINYAK JARAK PAGAR - Syahputri, Yulian; Mara, Adi (-)
Study of utilization of Natural Zeolites Active-Mo (Mo-ZAA) as a catalyst and influence of temperature variation on hydrocracking product temperature hydrocracking has done. Castor oil hydrocracking process done with a variation of the temperature of 250oC, 300oC, 350oC, 400oC, 450oC, 500oC and 550oC, flow rate of hydrogen gas 3.5 mL/minute and weighs 1.5 g catalysts. Hydrocracking castor oil products have been analyzed including the burning heat, density and viscosity by using the bom kalorimeter, picnometer and Ostwald viscometer instrument. The results of this study showed that the best value of the burning heat, density and viscosity in a row is on the 53.0003 kJ/g; 0.9698 g/mL and peace of 3.1691, each of which is operated at a temperature of 350oChydrocracking. Using the Mo-ZAA as a catalyst also plays a role in the process of hydrocracking. This can be seen from the value of the heat of combustion, the density and viscosity of castor oil hydrocracking product is better than the heat of combustion, density and viscosity prior hydrocracking. Key Words : Hydrocracking, Catalyst, Active Natural Zeolite, Castor Oil